Max Planck and the quantization of energy - Piattella, Oliver Fabio (Cadernos de Astronomia, 2023)
One of the founding ideas of Quantum Physics, the energy quantization, was put forward by Max Planck in the 1900 meeting of the German Physical Society. The paper derived from that talk is presented here in a direct translation from German to Brazilian Portuguese.